Hello!
When multiply binomials together, we should use the FOIL method.
The FOIL method is an acronym for First, Outer, Inner, and Last.
First, let's set up the expression.
(7x - 1)(3x - 2)
Now, we can multiply in accordance with the FOIL method.
First: 7x · 3x = 21x²
Outer: 7x · -2 = -14x
Inner: -1 · 3x = -3x
Last: -1 · -2 = 2
Now, we simplify the inner terms.
21x² - 14x - 3x + 2
21x² - 17x + 2
Therefore, the area of the rectangle is 21x² - 17x + 2.
Answer:
1/3 or .75 pounds of strawberries
Answer:
A su mamá
= 2937 pesos
A su hermano
= 1566.4 pesos
El resto para ella
= 3328.6 pesos
Step-by-step explanation:
El número total de pesos que cada uno consiguió se calcula como:
Su madre
= 3/8 del total
= 3/8 × 7832
= 2937 pesos
Su hermano
= 1/5 del total
= 1/5 × 7832
= 1566.4 pesos
Sí misma
= El resto
= 7832 - (2937 + 1566,4)
= 7832 - 4503.4
= 3328.6 pesos
The price of a painting in the year 2022 will be $ 568,000.
<h3>What is inflation?</h3>
A rise in the amount of a certain product or service is known as inflation.
Given data;
Cost of painting in the year 2021, P₁ = $560,000
Cost of painting in the year 2022, P₂ =?
The amount increases every year,x = $8,000
The cost of painting in the year 2022 is found as;
P₂ = P₁ + x
P₂= $560,000 + $8,000
P₂ = $ 568,000
Hence the price of a painting in the year 2022 will be $ 568,000.
To learn more about inflation refer;
brainly.com/question/19263433
#SPJ1
10.
Factor the following:
8 x^2 - 2 x - 10
Factor 2 out of 8 x^2 - 2 x - 10:
2 (4 x^2 - x - 5)
Factor the quadratic 4 x^2 - x - 5. The coefficient of x^2 is 4 and the constant term is -5. The product of 4 and -5 is -20. The factors of -20 which sum to -1 are 4 and -5. So 4 x^2 - x - 5 = 4 x^2 - 5 x + 4 x - 5 = 4 x (x + 1) - 5 (x + 1):
2 4 x (x + 1) - 5 (x + 1)
Factor x + 1 from 4 x (x + 1) - 5 (x + 1):
Answer: 2 (x + 1) (4 x - 5)
_____________________________________________
13.
Factor the following:
16 x^2 - 24 x + 8
Factor 8 out of 16 x^2 - 24 x + 8:
8 (2 x^2 - 3 x + 1)
Factor the quadratic 2 x^2 - 3 x + 1. The coefficient of x^2 is 2 and the constant term is 1. The product of 2 and 1 is 2. The factors of 2 which sum to -3 are -1 and -2. So 2 x^2 - 3 x + 1 = 2 x^2 - 2 x - x + 1 = -(2 x - 1) + x (2 x - 1):
8 x (2 x - 1) - (2 x - 1)
Factor 2 x - 1 from x (2 x - 1) - (2 x - 1):
Answer: 8 (2 x - 1) (x - 1)